2023
DOI: 10.29303/jppipa.v9i2.2915
|View full text |Cite
|
Sign up to set email alerts
|

Development of Magnetic Digital Comics in Science Learning to Improve Student Learning Outcomes in Elementary Schools

Abstract: This study aims to develop digital comics for learning magnetism in learning Science in Elementary Schools. This type of research is development research, which refers to the Four-D. The location of this research is at Kota Tengah 80 Public Elementary School, Bulangu Timur 1 Public Elementary School, and Telaga Biru 1 Public Elementary School. The results of the study show that digital comic magnets developed for science learning in elementary schools: (1) are categorized as valid and feasible; (2) Practically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Research results also showed that comic media can improve learning outcomes (Aisyah & Setiawan, 2023;Amali et al, 2023;Indriyani et al, 2024;Nada et al, 2019;Nasution et al, 2023), science literacy (Mutiaramses & Fitria, 2022), learning interest (Fatimah & Fatonah, 2023), creative thinking ability (Praptiwi et al, 2021), learning motivation and understanding concept (Safarati & Zuhra, 2023;Sukri, 2023).…”
Section: Introductionmentioning
confidence: 95%
“…Research results also showed that comic media can improve learning outcomes (Aisyah & Setiawan, 2023;Amali et al, 2023;Indriyani et al, 2024;Nada et al, 2019;Nasution et al, 2023), science literacy (Mutiaramses & Fitria, 2022), learning interest (Fatimah & Fatonah, 2023), creative thinking ability (Praptiwi et al, 2021), learning motivation and understanding concept (Safarati & Zuhra, 2023;Sukri, 2023).…”
Section: Introductionmentioning
confidence: 95%
“…The way to develop analytical and problem-solving skills in learning physics is to improve students' basic scientific literacy skills. According to Zulaiha et al (2021), scientific literacy is defined as the ability to understand scientific concepts and processes and use science to solve everyday problems or the ability to use scientific knowledge, define questions scientifically, draw conclusions based on scientific knowledge, change human nature and behavior as a result of human activity, and make decisions (Abdjul et al, 2022;Amali et al, 2023;Ntobuo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In education, a trendy term is known, namely the teaching and learning or learning process. Learning is an attempt to guide the student through the learning process to obtain learning objectives following what is expected (Amali et al, 2023;Djou et al, 2022;Hermanto et al, 2023;Payu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%